THE PROBLEM OF ETHNOPOLITICAL IDENTITY OF THE COSSACKS IN KABARDINO-BALKARIA IN THE LATE 20th AND EARLY 21st CENTURY - Shaozheva, N.A. (Perm Federal Research Centre Journal, 2016)
The processes relating to the politicization of ethnic identity of the Cossacks of the Kabardino- Balkarian Republic. It is shown that those processes were in many respects caused by general social, political and economic processes in Russia. Some factors, of both objective and subjective nature, contributing to the present renaissance of the Cossacks in the Kabardino-Balkariya Republic have been studied. Specific features of ethnopolitical identity of Cossacks at the present stage have been determined.